Comparison of Steroid and Botulinum Toxin Type A Monotherapy with Combination Therapy for Treating Human Hypertrophic Scars in an Animal Model. Issue 1 (July 2017) - Chen, Hung-Chang; Yen, Cheng-I; Yang, Shih-Yi; Chang, Cheng-Jen; Yang, Jui-Yung; Chang, Shu-Yin; Chuang, Shiow-Shuh; Hsiao, Yen-Chang
Abstract : Background: The authors evaluated the efficacy of a combined regimen of botulinum toxin type A (Botox) and a steroid (triamcinolone acetonide) for treating hypertrophic scars in comparison with the treatment with each drug alone. Methods: Twenty excised human hypertrophic scar fragments obtained from surgically treated burn patients were divided into four groups: negative control (group A), triamcinolone alone (group B), Botox alone (group C), and a combination of triamcinolone and Botox (group D). These specimens were implanted into the backs of nude mice after intralesional injection from each group and were observed for 4 weeks. In total, 12 mice and 48 scars were studied. After 4 weeks, the hypertrophic scars were removed from the backs. The authors compared the scar weights, decorin staining, and the Cell Counting Kit-8 assay to evaluate treatment efficacy. Results: Significant differences in scar weight reduction were observed among the four groups (group A, 10 percent; group B, 17 percent; group C, 23 percent; and group D, 30 percent; p < 0.05). Treatment groups (groups B, C, and D) showed strong decorin staining. Significant differences in reduction of fibroblast proliferation were observed among the four groups (group A, 0.58; group B, 0.44; group C, 0.21; and group D, 0.08; p < 0.05). Botox or triamcinolone intralesional monotherapy showed significant therapeutic efficacy compared with the control group. The combined therapy further exhibited a significant therapeutic effect compared with monotherapy. Conclusion: This study indicates the potential of Botox and triamcinolone when combined for intralesional therapy in treating hypertrophic scars. Abstract : Supplemental Digital Content is available in the text.